Combination of zingerone and dihydroartemisinin presented synergistic antimalarial activity against Plasmodium berghei infection in BALB/c mice as in vivo model. (June 2020) - Ounjaijean, Sakaewan; Somsak, Voravuth
Abstract: Malaria is a global health problem leading to the death of 435, 000 cases in tropical and sub-tropical zones. Spread and emergence of increasing resistance to the antimalarial drugs are the major challenges in the control of malaria. Therefore, searching for alternative antimalarial drugs is urgently needed, and combination treatment preferred as an approach to address this. This study aimed to evaluate in vivo antimalarial activity of zingerone (ZN), and its combination with dihydroartemisinin (DHA) against Plasmodium berghei infected mice. ZN was prepared and tested for acute oral toxicity according to the OECD guideline. In vivo antimalarial activity of different doses of ZN and combination with DHA were determined using the 4-day suppression test. The results showed that ZN was found to be safe and no mortality within the observation period, and the lethal dose might be greater than the limited dose of 1000 mg/kg. For in vivo antimalarial test, ZN exhibited significant ( p  < .05) parasitemia inhibition of 30.65% and 45.75% at the doses of 50 mg/kg and 100 mg/kg, respectively. Moreover, effective dose 50 (ED50 ) of ZN was 29.76 mg/kg. The combination treatment of ZN and DHA at the doses of ED50 values at the fixed ratio 1:1 was found to present significant ( p  < .001) antimalarial activity as compared to ZN and DHA treated alone with markedly prolonged mean survival time. Additionally, the combination index (0.83384) revealed the synergistic antimalarial effect. It can be concluded that ZN exerted potent antimalarial activity with no toxicity, and combination treatment with DHA produced the synergistic antimalarial effect. Graphical abstract: Unlabelled Image Highlights: Zingerone was found to be safe and no mortality at the dose levels up to 1000 mg/kg. Zingerone showed suppressive antimalarial activity against PbANKA. The ED50 values of ZN and DHA were 29.76 mg/kg and 1.92 mg/kg. Combination had the highest antimalarial activity with synergism.